Strengthening Reading Literacy and Scientific Inquiry as the Foundation of PAI Teacher Professionalism in the Era of Educational Transformation - Nasri (Formad English Foundation NTB-Jakarta, 2025)
This study explores the integration of reading literacy and scientific inquiry as foundational components in enhancing the professionalism of Islamic Religious Education (PAI) teachers amid ongoing educational transformation. Employing a qualitative literature review with a descriptive-analytical approach, the research systematically analyzed 20 peer-reviewed sources—comprising journal articles and scholarly books published between 2016 and 2024. The aim was to examine how the dual pillars of literacy and inquiry contribute to teacher competence in religious education settings. Findings indicate that reading literacy fosters interpretive depth, reflective thinking, and pedagogical clarity, particularly through critical engagement with religious texts. Simultaneously, scientific inquiry strengthens adaptability, informed classroom decision-making, and reflective teaching practices. The synthesis of these competencies not only addresses current pedagogical needs but also aligns epistemologically with core Islamic traditions, especially the principles of qira’ah (deep reading) and tadabbur (contemplative inquiry). A conceptual framework was developed to illustrate the reciprocal relationship between literacy and inquiry in shaping integrated teacher professionalism. This framework positions the teacher as both a reflective practitioner and a lifelong learner, capable of navigating between sacred knowledge and contemporary pedagogical demands. The study concludes that the integration of reading literacy and scientific inquiry provides a holistic and contextually grounded model for PAI teacher development. It offers practical implications for curriculum design, teacher education, and policy formulation, ensuring alignment with both Islamic educational values and 21st-century learning competencies.